2016
DOI: 10.1164/rccm.201508-1514oc
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bone Mineral Density in the Year after Critical Illness

Abstract: Critically ill individuals experience a significantly greater decrease in BMD in the year after admission compared with population-based control subjects. Their bone turnover biomarker pattern is consistent with an increased rate of bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 73 publications
12
62
0
Order By: Relevance
“…A very recent study found increased CTx and decreased serum PINP levels during ICU stay which is in accordance with our findings [9]. In addition to this study we found a commensurate response in bone formation markers during critical illness, that is, after the 3rd week of ICU stay as stated above.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A very recent study found increased CTx and decreased serum PINP levels during ICU stay which is in accordance with our findings [9]. In addition to this study we found a commensurate response in bone formation markers during critical illness, that is, after the 3rd week of ICU stay as stated above.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our study patients had during their ICU stay insufficient vitamin D serum levels, increased iPTH serum levels, and hypocalcaemia [9]. It was also suggested that vitamin D deficiency in critically ill patients with resultant secondary hyperparathyroidism along with prolonged immobilization and other metabolic abnormalities may increase the risk of excessive bone resorption [1, 17].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In recent years, an association between critical illness and accelerated bone turnover has been described, including an increase in bone turnover markers (BTM) during critical illness [18], accelerated loss of bone mineral density (BMD) in the year following critical illness [19], and increased fragility fractures in survivors of critical illness [20]. This association was, as expected, most pronounced in older women [19, 20].…”
Section: Introductionmentioning
confidence: 87%
“…Patients recovered from critical illness have been demonstrated to have decreased bone mineral density (BMD) [1]. The global awareness of long term consequences of critical illness is rapidly increasing, but the identification of specific pathophysiological mechanisms is still tentative.…”
Section: Introductionmentioning
confidence: 99%